Anaerobic threshold load indicators for speed endurance during fasting on 500m performance - Benchaira, zoubir; guellati , yazid; guermat, nouri (sports creativity, 2024)
The objective of this study is to identify the anaerobic threshold indicators during speed endurance, and to analyze its impact on performance while fasting and after breakfast. The investigation involves a comparative analysis of performance outcomes between runners. The sample group consists of seven male runners below the age of 18 who are members of the Biskra Athletics Club in Algeria. The Researchers employed, the 500m running test to determine the anaerobic threshold indicators for performance, and statistical analyses to examine performance characteristics and variances. The findings of the study reveal notable disparities in performance levels between the initial and latter phases of the fasting period.